Use of complementary and alternative medicines for children with chronic health conditions in Lagos, Nigeria - Oshikoya, Kazeem A (BioMed Central, 2008)
BACKGROUND: The use of complementary and alternative medicine (CAM) is on the increase globally with a high prevalence in children and adults with chronic illnesses. Many studies have evaluated the epidemiology of medicine use for children in developing countries but none has evaluated the use of CAM for children with chronic illnesses. The aim of this study was therefore to determine the prevalence, pattern of use, parental sources of information, perceived benefits, cost, and adverse effects of CAM in children with epilepsy, sickle cell anaemia and asthma in Lagos, Nigeria. METHODS: Parents of children with epilepsy (122), asthma (78) or sickle cell anaemia (118) who presented consecutively to the paediatric neurology, respiratory and haematology clinics of the Lagos State University Teaching Hospital (LASUTH), Ikeja were interviewed with a structured open- and close-ended questionnaire. The information obtained comprised the demography of both the patients and their parents; past and present treatments received by the patients; the type of CAM, if any, used by the patients; and the sources, cost, benefits and adverse effects of the CAM used. RESULTS: A total of 303 CAMs were used by the patients, either alone or in combination witother CAM. CAM was reportedly used by 99 (31%) patients (epilepsy -38%, sickle cell anaemia – 36% and asthma – 25%). The majority (84%) of these patients were currently using CAM. The use of CAM was stopped six months prior to the study by 16 patients (16%). Biological products were the most frequently used CAMs (58%), followed by alternative medical systems (27%) and mind-body interventions (14%). Relations, friends and neighbours had a marked influence on 76% of the parents who used CAM for their children. Eighty-five (86%) parents were willing to discuss the use of CAM with their doctors but were not asked. CAM use was associated with adverse reactions in 7.1% of the patients. CONCLUSION: Parental use of CAMs to treat their children with epilepsy, asthma and sickle cell anaemia is common in Nigeria. Efforts should be made by doctors taking care of these patients to identify those CAM therapies that are beneficial, harmless and cheap for possible integration with conventional therapy.